Moral Values of Pancasila for Building the Nation in the Era of Globalization - Dinda Anastasiya (International Journal of Students Education, 2024)
The purpose of writing this article is to describe and explain how Pancasila can play a role, be implemented and actualized in the context of globalization, with the aim of increasing morality in an effort to build and advance the nation. This research method is a qualitative approach that describes the role of Pancasila in the era of globalization to strengthen morality for the progress of the nation. This research uses a qualitative method or descriptive approach, taking sources from various literature. The results of the analysis show that globalization brings changes in people's lives, and Pancasila has an important role in responding and adapting to new information, especially to maintain the identity of the Indonesian nation, especially the younger generation, so that it remains connected to the values of Pancasila. Pancasila, in this context, has a very important role in maintaining and maintaining the values contained in it. Pancasila is also expected to be able to continue to filter and select information and new values that come in, so that these values can continue to be used as a moral foundation for the nation. Therefore, re-instilling Pancasila values is important to build and advance the nation.